Dental anxiety and the association with psychological symptoms among adults attending IIUM Kuantan health facilities - Mohd, Farah Natashah; Said, Abdul Hadi; Maluin, Nur 'Afirah; A Rahaman, Nabila; Ibrahim, Nurul Ruziantee (2021)
Dental anxiety is a condition in which the patient will have overwhelming sense of fear by feeling threatened of any dental treatment. Klingberg, G. & A. Broberg (2007) • Dental anxiety may worsen the oral health as people with dental anxiety tend to delay or avoid dental treatment. Armfield, J., G. Slade, & A. Spencer (2009) • There are evidence showing positive correlation between general anxiety and dental anxiety. G.Pekkan 2011 • Most studies done on dental anxiety in Malaysia focused on ante natal mothers, children and teenagers.